2016
DOI: 10.1002/bdd.2027
|View full text |Cite
|
Sign up to set email alerts
|

Cyp3a11‐mediated testosterone‐6β‐hydroxylation decreased, while UGT1a9‐mediated propofol O‐glucuronidation increased, in mice with diabetes mellitus

Abstract: The db/db mouse is one of the most popular animal models for type 2 diabetes mellitus, but changes in the activities of important P450s and UGTs are still not completely clear. This study was designed to investigate the alterations of major hepatic cytochrome P450s and UDP-glucuronyltransferase enzymes in db/db mice. Mouse liver microsomes (MLMs) were obtained from male db/db mice and their wild type littermates. After incubation of the substrates separately with MLMs, the samples were pooled and analysed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Glucuronidation is used to assist in the kidney excretion of toxic substances, drugs or other substances. It showed that activity of UDP glucuonyltransferase, catalyzing glucuronidation process was increased in diabetes mellitus mice model 33 . GDM is considered as the pre-diabetes stage, which may has similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronidation is used to assist in the kidney excretion of toxic substances, drugs or other substances. It showed that activity of UDP glucuonyltransferase, catalyzing glucuronidation process was increased in diabetes mellitus mice model 33 . GDM is considered as the pre-diabetes stage, which may has similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As for M2, our results showed that the hepatic biotransformation of berberine into M2 was decreased and its intestine bacterial biotransformation was increased. For the phase II metabolites, their increased plasma concentrations and urinary excretions might be owed to the regulation of UDP-glucuronosyltransferase and sulfotransferase activities in diabetes 29 , 30 . The decreased biliary excretions of the five phase II metabolites might be caused by the structure and function changes of the bile duct under diabetic disease conditions 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Mouse liver/intestine microsomes and HEK3a11 cell lysate were prepared as previously described 13,52 . In vitro metabolic activity was determined using the published incubation procedures 53 . After 2-h-incubation at 37 °C, the reactions were terminated by adding ice-cold acetonitrile.…”
Section: Methodsmentioning
confidence: 99%